Riqueza y abundancia de aves en época de creciente en Moronacocha, Iquitos – Perú - Loja Alemán, Eduardo Antonio (2023)
From february to april 2021, I study the richness and abundance of birds in season flooded in Moronacocha – Iquitos city, by boat census and hearing recognition. I report a richness of 15 órdenes with predominance Passeriformes, Columbiformes, Pelecaniformes, Accipitriformes, Cathartiformes and Psittaciformes, with 24 families and a specific richness of 67 species. Relative abundance was, a general level, for Cacicus cela (11.02 ind/km), Psarocolius angustifrons (6.76 ind/km), Psittacara leucophthalma (3.64 ind/km), Tyrannus savana (3.52 ind/km) and Butorides striata (3.05 ind/km), and density for Cacicus cela (367 ind/km2), as well Psarocolius angustifrons (225 ind/km2), Chrysomus icterocephala (133 ind/km2) y Psittacara leucophthalma (121 ind/km2). I concluded what the specific richness of birds in season flooded in Moronacocha was high with predominance of species of the Passeriformes order.